Ceftaroline modulates the innate immune and host defense responses of immunocompetent cells exposed to cigarette smoke. (5th September 2017) - Bruno, A.; Cipollina, C.; Di Vincenzo, S.; Siena, L.; Dino, P.; Di Gaudio, F.; Gjomarkaj, M.; Pace, E.
Highlights: Cigarette negatively influences the immune system's response to a pathogen. Ceftaroline is a prodrug used to treat Community Acquired Pneumonia. Ceftaroline counteracts the effect of smoke in immunocompetent cells. Ceftaroline increases anti-microbial host defense activities. Abstract: Background: Cigarette smoke, the principal risk factor for chronic obstructive pulmonary disease (COPD), negatively influences the effectiveness of the immune system's response to a pathogen. The antibiotic ceftaroline exerts immune-modulatory effects in bronchial epithelial cells exposed to cigarette smoke. Aims and methods: The present study aims to assess the effects of ceftaroline on TLR2 and TLR4 expression, LPS binding and TNF-α and human beta defensin (HBD2) release in an undifferentiated and PMA-differentiated human monocyte cell line (THP-1) exposed or not to cigarette smoke extracts (CSE). TLR2, TLR4, and LPS binding were assessed by flow cytometry, TNF-α and HBD2 release were evaluated by ELISA. Results: The constitutive expression of TLR2 and TLR4 and LPS binding were higher in differentiated compared to undifferentiated THP-1 cells. In undifferentiated THP-1 cells, CSE increased TLR2 and TLR4 protein levels, LPS binding and TNF-α release and reduced HBD2 release and ceftaroline counteracted all these effects. In differentiated THP-1, CSE did not significantly affect TLR2 and TLR4 expression and LPS binding but reduced HBD2 release and increased TNF-α release. Ceftaroline counteracted the effects of CSE on HBD2 release in differentiated THP-1. Conclusion: Ceftaroline counteracts the effect of CSE in immune cells by increasing the effectiveness of the innate immune system. This effect may also assist in reducing pathogen activity and recurrent exacerbations in COPD patients.